2007
DOI: 10.1016/j.ijhydene.2006.06.061
|View full text |Cite
|
Sign up to set email alerts
|

Progress in high-temperature electrolysis for hydrogen production using planar SOFC technology

Abstract: A research program is under way at the Idaho National Laboratory to assess the performance of solid-oxide cells operating in the steam electrolysis mode for hydrogen production over a temperature range of 800 to 900ºC. The research program includes both experimental and modeling activities. Selected results from both activities are presented in this paper. Experimental results were obtained from a ten-cell planar electrolysis stack, fabricated by Ceramatec 1 , Inc. The electrolysis cells are electrolyte-suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
155
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(159 citation statements)
references
References 2 publications
3
155
0
1
Order By: Relevance
“…Because of its good ionic conductivity at high temperatures (873 -1273K), yttria-stabilized zirconia (YSZ) has been widely used as an electrolyte material in solid oxide fuel cells (SOFCs) for electricity generation and solid oxide electrolysis cells (SOECs) for H 2 generation through steam electrolysis [1][2][3][4][5][6][7][8]. In addition to steam electrolysis, SOECs can also be used for CO 2 electrolysis to generate O 2 [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its good ionic conductivity at high temperatures (873 -1273K), yttria-stabilized zirconia (YSZ) has been widely used as an electrolyte material in solid oxide fuel cells (SOFCs) for electricity generation and solid oxide electrolysis cells (SOECs) for H 2 generation through steam electrolysis [1][2][3][4][5][6][7][8]. In addition to steam electrolysis, SOECs can also be used for CO 2 electrolysis to generate O 2 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some valuable modeling studies on steam electrolysis for H 2 production using SOECs [5][6][7][8], a pertinent modeling or reliable analysis on CO 2 electrolysis is needed to understand the physical-chemical processes in an SOEC used for CO 2 electrolysis. Chan et al [13] developed an electrolyte model for CO 2 electrolysis, however, the important gas transport phenomenon in porous electrodes was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 shows a schematic for one possible configuration of the NGNP, and Figure 5 shows the tritium material balance calculated for this configuration using the THYTAN model. In this configuration, a 600 MWt VHTR is used to generate electricity and to provide high-temperature heat to a high-temperature steam electrolysis (HTSE) plant used for making hydrogen [31]. Three heat transfer loops are assumed -a primary loop, a secondary loop, and a tertiary loop.…”
Section: Tritium Mass Balancesmentioning
confidence: 99%
“…Studies of the experimental operation of SOECs can be found in several publications. Herring et al [12] showed that the stack performance is dependent on the inlet steam flow rate based on the experimental measurement and modelling study 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w 6 of a 10-cell stack. Schiller et al [11] studied the electrochemical performance of an SOEC, and the structure of the materials at different temperatures and current densities, and tested the durability of the stack.…”
mentioning
confidence: 99%
“…Brisse et al [13] paid special attention to the impedance behaviour of the SOEC operated at different temperatures, current densities and steam concentration. All these experimental studies of the SOEC (at the cell level and the stack level) are carried out in a furnace where the temperature is maintained at a constant level, although a temperature distribution within the stack has been reported [12].…”
mentioning
confidence: 99%